Job Resourcefulness, Customer Orientation and Employees Outcomes: A Study of Hotel Employees in Pakistan - Fatima, Afsheen; Uddin, Sarah Salah; Mehmood, Saba; Bibi, Ashfeen (Information Management and Business Review, 2018)
Increased competition and a rapidly changing environment present a huge challenge to organizations in implementing effective human capital and development strategies to boost their efficiency and overall performance. An organization’s human resource is definitively its most significant asset. The provisions of important job resources help workforce perform their job in an efficient way. These resources are very important for employee satisfaction and performance of the organization. This study was carried out to examine the impact of job resourcefulness (JR) on two employee outcomes i.e., job engagement and career satisfaction directly as well as indirectly through customer orientation. A convenient sample of 257 employees was taken from hospitality industry within twin cities of Pakistan (Rawalpindi and Islamabad). Questionnaires were used to collect data using a five-point Likert type scale. Job resourcefulness was operationalized using four items from Harris et al. (2006) whereas customer orientation was measured using four items from Licata et al. (2003). Five items were selected from career satisfaction scale developed by Greenhaus et al. (1990). Finally, nine items scale of job engagement developed by (Schaufeli, Bakker et al. 2006) was also used. The results exhibit that all the variables are positively and significantly related. Moreover, the findings are indicative of customer orientation’s role as a mediator between job resourcefulness and employee outcomes. Recommendations for future research and research implications are also discussed at the end of the paper.